Analisa Pengembangan Materi IPS Di Era Globalisasi Di MI Ma'arif NU 01 Kajongan - Rahma, Annisa Auwla; Ningsih, Tutuk (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
The era of globalization is an order of human life that globally involves all humanity. The era of globalization can lead to changes in the lifestyle of a more modern society. The process of globalization begins with the existence of information technology that is developing rapidly. Information technology has progressed in the development of one of its creations, namely the internet. This research uses a qualitative method with a case study approach at MI Ma'arif NU 01 Kajongan to examine various relevant cases in answering how the development of social studies materials in the era of globalization in MI Ma'arif NU 01 Kajongan. The research stages consist of data collection, observation and interviews, data classification, and conclusion. The results of the analysis show that social studies learning in this era emphasizes the ability of students to seek information from various sources, then formulate problems, think critically, and cooperate and collaborate to solve problems. Improving the quality of human resources through education ranging from primary and secondary education to higher education is the key to being able to keep up with the development of the Era of Globalization. Keywords :Social Science Studies, Globalization era, Technology